Acylhomoserinlactones – the latest regulators of stress resistance and yield of agricultural crops - Babenko, Lidiia; Kosakivska, Iryna; Voitenko, Lesia; Romanenko, Kateryna (Problems of Environmental Biotechnology, 2021)
Acyl homoserine lactones (AHL) are a class of mediator molecules of bacterial origin involved in the remote transduction of signals between bacteria-colonizers of the phytosphere, as well as between bacteria and plants.